ANALYSIS OF ACAD CONSTRUCTION ON SHARIA ONLINE LOANS AT PT DUHA MADANI SYARIAH - MUALLIFATUR ROSIDAH; JAMAL ABDUL AZIZ; MUNTAHA MAHFUD (JEBI (Jurnal Ekonomi dan Bisnis Islam), 2023)
Technological developments in the field of information and communication have had a major impact on the digitalization of finance, especially with the presence of a new innovation called financial technology. One such fintech is Duha Syariah. This study aims to analyze the construct of sharia online financing contracts at PT Duha Madani Syariah from the perspective of Sharia Economic Law. While this research uses library research. Normative juridical approach. Source of data using primary data and secondary data. Data collection techniques using documentation. Data analysis consists of data reduction, data categorization, and data synthesis.The construct analysis of the sharia online financing contract at PT Duha Madani Syariah uses a Murabahah contract, Duha Syariah gives a certain amount of money to the customer to buy the desired item, then Duha Syariah gets a margin from the purchase of the item, and the customer makes installment payments to Duha Syariah.